1965
DOI: 10.1149/1.2423480
|View full text |Cite
|
Sign up to set email alerts
|

The Active Iron Electrode

Abstract: The pH and potential dependencies of the steady‐state iron dissolution and hydrogen evolution reactions were determined for zone‐refined iron in H2‐saturated acidic sulfate solutions. The mechanistic significance of the data is examined in detail. The results of this investigation serve to resolve the conflict concerning the mechanism of iron dissolution in noninhibiting media and to provide an experimental and mechanistic base for the interpretation of the electrochemical behavior of the active iron electrode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
75
0
2

Year Published

1965
1965
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(85 citation statements)
references
References 15 publications
8
75
0
2
Order By: Relevance
“…This indicates that the mechanism of corrosion process is different at lower concentration levels and higher concentration levels; and mechanism remaining the same within the concentration ranges mentioned at both the levels. The values of cathodic Tafel slopes at higher concentration ( b c , 120 mV/dec) suggest that the hydrogen evolution reaction (HER) is independent of sulphate ion concentration, the rate determining step in the HER is the discharge reaction, a result which agrees with previous works [17,[28][29].…”
Section: Effect Of Concentrationsupporting
confidence: 90%
See 1 more Smart Citation
“…This indicates that the mechanism of corrosion process is different at lower concentration levels and higher concentration levels; and mechanism remaining the same within the concentration ranges mentioned at both the levels. The values of cathodic Tafel slopes at higher concentration ( b c , 120 mV/dec) suggest that the hydrogen evolution reaction (HER) is independent of sulphate ion concentration, the rate determining step in the HER is the discharge reaction, a result which agrees with previous works [17,[28][29].…”
Section: Effect Of Concentrationsupporting
confidence: 90%
“…This may be due to the change in hydrogen overvoltage, which in turn affects the cathodic polarization curve. This may be also due to the contribution from concentration polarization [17], which leads to deviation of cathodic curve from Tafel behavior at lower cathodic potentials, since the variation in b c is more prominent at lower concentrations of acid. In aged specimen Tafel slopes remain approximately the same.…”
Section: Effect Of Temperaturementioning
confidence: 99%
“…Many previous studies of hydrogen evolution reaction on pure iron have shown that the Volmer reaction is appropriate as the ratedetermining step. 25,[27][28][29] Thus, hydrogen evolution reactions on pure iron and cast iron are found to be the same.…”
Section: Mechanism Of Hydrogen Evolution Reaction On Cast Ironmentioning
confidence: 68%
“…This value is two or five orders of magnitude lower than that of pure iron composed of only ferritic matrix. 25 It is inferred that the rate of hydrogen evolution reaction of graphite particles in the cast iron is the same as that of the graphite electrodes. Thus, the cathodic current density of hydrogen evolution reaction on graphite particles Electrochemistry, 82(2), 104-108 (2014) in cast iron matrix is considered to be negligible.…”
Section: Cathodic Current Due To Hydrogen Evolution Reactionmentioning
confidence: 98%
“…(29)], the total current density is given by (cf. Stern(23)) (30) This equation resembles the Butler-Volmer equation for a single reaction, where the corrosion potential and corrosion current density have replaced the equilibrium potential and exchange current density. The primary justification for writing the equation in this form is to describe the corrosion kinetics concisely and economically.…”
Section: Icathodicmentioning
confidence: 99%